Microwave dielectric properties of (KY)1/2MoO4 ceramics with ultra-low sintering temperature. (March 2023) - Wang, Xiao-Long; Pang, Li-Xia; Zhou, Di; Fang, Zhen; Ren, Sen; Liu, Wei-Guo
Abstract: The compound (KY)1/2 MoO4 in K2 CO3 -Y2 O3 -MoO3 system was fabricated via the solid-state reaction method, and the (KY)1/2 MoO4 ceramics were obtained at ultra-low sintering temperatures. Scanning electron microscopy results demonstrated that all the (KY)1/2 MoO4 ceramics could be densified well in the sintering temperature scope of 620–660 °C. X-ray diffraction results indicated that all the (KY)1/2 MoO4 ceramics crystallized into the orthogonal structure with space group Pbcn (60) and no heterophase formation. The (KY)1/2 MoO4 ceramics sintered at 640 °C for 2 h exhibited the optimal microwave dielectric properties, with a microwave permittivity of 9.6, a Q × f value of 25, 550 GHz, and a TCF value of − 37.5 ppm/°C. 20 wt % aluminum and/or silver powders were mixed with (KY)1/2 MoO4 and co-fired at 640 °C, the results showed that the (KY)1/2 MoO4 ceramics displayed good chemical compatibility with potential electrodes Al and Ag. Because of the ultra-low sintering temperature, good microwave dielectric properties and chemical compatibility with Al and Ag, the (KY)1/2 MoO4 ceramic was expected to be a potential candidate for ultra-low temperature co-fired ceramic (ULTCC) technology. Graphical Abstract: ga1 Highlights: The (KY)1/2 MoO4 ceramics were prepared via the solid-state reaction method. The ceramics structure was analyzed and lattice parameters were investigated. Permittivity of 9.6, Q×f value about 25, 550 GHz, and TCF value of 37.5 ppm/ °C were obtained. The ceramics present excellent chemical stability with Al or Ag.